ANALISIS PENERAPAN PSAP NO. 1 TENTANG PENYAJIAN LAPORAN KEUANGAN PADA UPTD PUSKESMAS GUNUNG PATI SEMARANG - Tasya Rifanis Shofia; Siti Mutmainah; Nikmatuniayah Nikmatuniayah (Politeknik Negeri Semarang, 2020)
Regional Technical Implementation Unit (RTIU) Gunung Pati Public Health Center is a Regional Public Service Agency for the City of Semarang which has the obligation to compile financial reports to meet the demands of transparency and accountability to society. The drafting is using a computer-based application, namely e-BLUD. This application was still incomplete while the operation, which can cause errors in the process of drafting the financial reports. The purpose of this study is to analyze the suitability of the financial reports of the RTIU Gunung Pati Public Health Center with Government Regulation No. 71. The data is used qualitative, quantitative, primary and secondary data. The data collection used interview method, literacy and documentary. The results of this research show that the financial statements of the RTIU Gunung Pati Public Health Center are relatively accordance with Government Regulation no. 71 concerning Government Accounting Standards.